Early Diagnosis of Epilepsy Syndromes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The classification of epilepsy syndromes made initially on the basis of information at time of diagnosis was compared to that made 2 years later in a cohort of 613 children, followed by participating physicians in Connecticut, between 1993 and 1997.